Specialities of the corporate tax in connection with the sports organizations - Herczeg, Adrienn; Dékán Tamásné Orbán, Ildikó; Becsky-Nagy, Patrícia; Fenyves, Veronika (Applied Studies in Agribusiness and Commerce, 2015)
In 2004 Hungary joined the EU, therefore its tax system is harmonized with EU directives and its trade with the EU is liberalized and exempt from customs restrictions. In the past few years Hungarian government introduced significant corporate tax advances in order to increase Hungary’s competitiveness for foreign capital. With the flat 10% corporate tax rate, Hungary has one of the the lowest corporate income tax rate in the European Union. Since 2011 new corporate tax incentive was adopted in order to create a tax advantageous economic environment for supporting the five most popular team sports in Hungary, namely, football, handball, basketball, water polo and ice hockey. The following article provides a rough guide on the corporate taxation – in particular of sport organizations in Hungary. JEL code: H25